LEVEL KEMAMPUAN MAHASISWA DALAM MENYELESAIKAN SOAL PENALARAN STATISTIS - Nila Kesumawati; Dina Octaria (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Statistical reasoning is the ability to explain why and how conclusions are obtained. Statistical reasoning is very necessary in everyday life, as well as in basic statistics and research statistics. Statistical reasoning is divided into 5 levels, namely 1) LPS 0 (does not have statistical reasoning), 2) LPS 1 (prestructure reasoning), 3) LPS 2 (transitional reasoning), 4) LPS 3 (procedural reasoning), 5) LPS 4 (integrated reasoning). This study aims to determine the level of students' ability to work on statistical reasoning questions. This research was carried out in the second semester students with the number of research subjects 80 students in the mathematics education study program at the University of PGRI Palembang. The research method used is descriptive research, with data collection techniques using tests and interviews. The results of the study show that the ability of students to solve statistical reasoning problems is at level 3 (procedural reasoning).